MINAT SISWA KELAS IV SDN TURI 1 TERHADAP PEMBELAJARAN DARING MENGGUNAKAN GOOGLE FORMULIR - Hidayatul Muslimah; Wulida Arina Najwa (Program Studi Pendidikan Guru Sekolah Dasar STKIP Al Hikmah Surabaya, 2020)
The Covid-19 pandemic has made major changes in the teaching and learning process in Indonesia. Online learning that is suddenly implemented, makes the teacher have to work hard to make learning that does not burden students and does not reduce the essence of learning itself. Various applications are used, one of which is google forms. This study uses a descriptive approach with the aim of describing the level of student interest in online learning using google forms. The subjects of this study were fourth grade students of SD Negeri Turi 1 in the 2019/2020 academic year consisting of 12 male students and 15 female students. The data collection technique used in this study used a questionnaire. Based on the results of the questionnaire, it can be seen that 19 students or 70% of students showed a very good predicate on their interest in learning in learning using Google Forms. As many as 8 students or 30% of students showed a good predicate on their interest in learning in learning using Google Forms. There are no students who have sufficient or less interest in learning using Google Forms.